Synergy between Badan Amil Zakat Nasional and Badan Wakaf Indonesia to Strengthen Waqf Assets in Central Java - Septiana, Yunita Dewi; Nuriyyatiningrum, Mahdaniyal Hasanah; Munawaroh, Lathifah Lathifah; Nadia, Rouahna Rouahna (Magister Hukum Universitas Semarang, 2025)
This research aims to analyze the synergy between Badan Amil Zakat Nasional (Baznas) and Badan Wakaf Indonesia (BWI) and to examine the obstacles and impact of synergy between both. Baznas and BWI are the two government agencies tasked with managing the muslim community assets; Baznas is tasked with collecting and utilizing zakat, while BWI is responsible for managing waqf assets. The zakat funds collected by Baznas are relatively large, but many have not been distributed. On the other hand, BWI has many waqf assets but does not have the funds to make them productive. Based on the strengths and weaknesses of each, cooperation between the two is crucial to be strengthened. This article is a qualitative research with a normative-empirical approach. The results of the research show that the synergy between the two is held in communication and coordination. The obstacles to synergy are related to funding for asset development, nazir's professionalism, lack of legalization of waqf assets. The synergy between Baznas and BWI has not had a significant impact on the development of productive waqf assets in the Central Java province. If both work together synergistically, they can generate a more beneficial and productive waqf for the ummah, as seen in the case of the Johar Market relocation and the establishment of healthcare services in the form of hospitals for the benefit of the community. This article complements the theme around the importance of synergy between waqf institutions so that the benefits of waqf and the sustainability of its management can run optimally, just as the commitment of both institutions to financial reporting is important, making nazir more professional can be achieved by providing training and establishing partnerships with other, more competent institutions.